Low knowledge about hepatitis B prevention among pregnant women in Kinshasa, Democratic Republic of Congo. - Sahal Thahir; Samantha E Tulenko; Patrick Ngimbi; Sarah Ntambua; Jolie Matondo; Kashamuka Mwandagalirwa; Martine Tabala; Didine Kaba; Marcel Yotebieng; Jonathan B Parr; Peyton Thompson (Public Library of Science (PLoS), 2022)
Infants infected perinatally with hepatitis B (HBV) are at the highest risk of developing chronic hepatitis and associated sequelae. Prevention of mother-to-child transmission (PMTCT) of HBV requires improved screening and awareness of the disease. This study evaluated existing HBV knowledge among pregnant mothers (n = 280) enrolled in two HBV studies in urban maternity centers in Kinshasa, Democratic Republic of the Congo. All mothers responded to three knowledge questions upon study enrollment. Baseline levels of knowledge related to HBV transmission, treatment, prevention, and symptoms were low across all participants: 68.8% did not know how HBV was transmitted, 70.7% did not know how to prevent or treat HBV MTCT, and 79.6% did not know signs and symptoms of HBV. Over half of participants responded "I don't know" to all questions. HBV-positive women who participated in both studies (n = 46) were asked the same questions during both studies and showed improved knowledge after screening and treatment, despite no formal educational component in either study (p < 0.001). These findings highlight the need for intensified education initiatives in highly endemic areas to improve PMTCT efforts.